Digital Transformation in Education: Awareness of Quality Management Systems Among Elementary Teachers in San Francisco District - Gevero, Reymart Ray; Oropa, Jane (Journal of Interdisciplinary Perspectives, 2025)
In the digital age, the effective management of documents has become a pivotal challenge for elementary school teachers, as technology reshapes educational practices. Using a descriptive correlational research design, this study assessed the level of awareness of the digitalized quality management system among elementary school teachers in the San Francisco District of Agusan del Sur Division. Data were collected from teachers through a validated questionnaire and analyzed to identify patterns and relationships. The findings revealed that teachers positively perceived the digitalized system, with significant correlations between awareness levels and factors such as length of service and academic rank. Specifically, teachers with longer service and higher academic ranks demonstrated higher awareness levels. The study identified areas needing improvement, particularly in document security and digital tools. To address these gaps, an action plan was developed for a comprehensive training program, including preparatory activities, needs assessment, curriculum planning, resource preparation, collaborative sessions, continuous monitoring, and stakeholder engagement. The results highlight the critical need for targeted training and continuous support, leveraging the expertise of experienced educators, and ensuring the availability of resources and professional development opportunities. These efforts are expected to enhance teachers' proficiency with digital tools and document security, improving the quality of education. The study's findings have significant policy implications, emphasizing the need for educational policymakers to integrate digital tools in teacher training programs, allocate resources for continuous professional development, and establish robust support systems to enhance the effectiveness of digitalized quality management systems in schools. By implementing these measures, the study aims to foster a more efficient and secure educational environment in the division of Agusan del Sur.